An intrusion breccia with associated ultrabasics from Sermersût, South-West Greenland - Bondesen, Erling (Meddelelser om Grønland, 1964)
A detailed 1:500 map and a description of some peculiar breccia structures are presented. The breccia was emplaced in the Precambrian basement rocks, consisting mainly of granodioritic gneisses and amphibolites. The structures of the breccia are highly irregular consisting of lots of connected dyke-shaped bodies. More distinct dykes of the breccia matrix run out into the gneisses. The breccia itself consists of a matrix of mineral fragments and numerous inclusions of rock fragments, the majority of which are of exotic origin. Associated with the breccia are some larger soapstone bodies of which smaller fragments are found in the breccia. The breccia is thought to have been emplaced by gas drilling in connection with the intrusion of the soapstones in a solid /subsolid stage. The chronological significance of the breccia is emphasized.